2016
DOI: 10.4045/tidsskr.14.1574
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of M. genitalium and U. urealyticum in urine tested for C. trachomatis

Abstract: 121Originalartikkel Forekomst av M. genitalium og U. urealyticum i urin testet for C. trachomatis 121 -5 Liv RESULTATER Forekomsten av C. trachomatis, M. genitalium og U. urealyticum var henholdsvis 11,9 %, 3,6 % og 17,9 %. M. genitalium forekom hyppigst hos kvinner i alderen 20 -24 år (5,1 %), mens det var størst andel positive prøver med U. urealyticum hos personer i alderen 15 -24 år (22,8 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Depending on the causative pathogen, STIs show unspecific symptoms, such as dysuria, urethral or vaginal discharge, pelvic pain and acyclic bleeding, but have serious reproductive health consequences beyond the immediate impact of the infection itself [3]. Symptoms of Mycoplasma and Ureaplasma infection are mild, but a chronic colonization leads to latent disturbed natural microbial flora and might increase the risk of acquisition of other pathogens [4]. Further they are associated with pelvic inflammatory disease (PID), which might lead to infertility [5,6], and intra amnionic and postpartum infections.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the causative pathogen, STIs show unspecific symptoms, such as dysuria, urethral or vaginal discharge, pelvic pain and acyclic bleeding, but have serious reproductive health consequences beyond the immediate impact of the infection itself [3]. Symptoms of Mycoplasma and Ureaplasma infection are mild, but a chronic colonization leads to latent disturbed natural microbial flora and might increase the risk of acquisition of other pathogens [4]. Further they are associated with pelvic inflammatory disease (PID), which might lead to infertility [5,6], and intra amnionic and postpartum infections.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Present study also revealed that 4.8% of women with C. trachomatis and 11% of women with M. hominis also had M. genitalium infection, which is lower when compared to 9% of C. trachomatis - M. genitalium co-infected women that underwent population-based screening in London[8] and 11% in a screening study conducted in Norway. [9]…”
Section: Discussionmentioning
confidence: 99%
“…La oss starte med et eksempel. Paulsen og medarbeidere beskrev forekomsten av positive funn for tre forskjellige infeksjoner i urinprøver (1)…”
Section: Inntil Tre Hendelserunclassified